Developing Discovery-Based Writing Assessments to Stimulate Students’ Critical Thinking and Creativity - Nurwachid, Nurwachid (English Education Journal, 2018)
The implementation of 2013 curriculum demanded English teacher to be able to use and develop assessments that is able to make students critical and creative. However, most of them did not develop the assessments that were able to stimulate students’ critical thinking and creativity. This study aimed to explain the development of discovery-based writing assessments to stimulate students’ critical thinking and creativity. It was conducted at the tenth graders of MA Manbaul Quran. The method used in this research was research and development (R&D). To get the data, researcher used observation, questionnaire, interview and test. The results of the study showed that developing discovery based writing assessments were effective to make students critical and creative in writing English text. It also showed that the students’ score of post-test was higher than pre-test. The mean score of pre test was 56,85 and the mean score of post test was 74,05. The critical thinking of the students was seen through their ability to synthesize ideas, evaluate ideas, and draw the conclusion. The creativity of the students was seen through their ability to synthesize ideas, use different point of views, generate and select alternative. The result also showed that students were interested in doing the activities during the treatment. The activities could help the students to be creative and critical in writing English text. In conclusion, developing discovery-based writing assessments was effective to stimulate students’ creativity and critical thinking.